Diseño de una mezcla asfáltica incorporando fibra de abacá con cal como materiales de refuerzo al comportamiento Marshall - Romero Loayza, Hugo Fabian (2022)
The purpose of this Project is to propose an alternative to improve the properties of an asphalt mixture with abaca fiber and lime as an alternative material. For its development, the stone materials, asphalt and lime were obtained in the Chimborazo province, the abaca fiber acquired in Santo Domingo city, and their characterization was carried out through laboratory tests to verify regulatory compliance. Once the characteristics of the materials were defined, we proceeded to work with a design previously prepared and used by COVIPAL's asphalt plant, with the Marshall design methodology, where several briquettes were prepared and tested for each of the following percentages of lime (1.5%, 2.5% and 3.1%) and three with the addition abaca fiber in percentages of 0.5%, 1% and 1.5% with the same content of lime and asphalt. The results obtained in the research showed that the modified mixture of 2.5% lime and 0.5% abaca fiber had the best characteristics with a stability increase of 21.26% compared to the traditional mixture, and the flow rate reduced from the average value of 13.9 in/100 of the conventional mix to 13.67 in/100. By implementing abaca fiber and lime in the asphalt mixture, the mechanical stability property improved, while the percentage of voids exceeded the limits allowed by the standard